Cervical Mesonephric Adenocarcinoma: A Case Report of a Rare Gynecological Tumor from Embryological Remains of the Female Genital Tract - Reis-de-Carvalho, Catarina; Vaz-de-Macedo, Carolina; Ortiz, Santiago; Colaço, Anabela; Calhaz-Jorge, Carlos (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2021)
Introduction Malignant mesonephric tumors are uncommon in the female genital tract, and they are usually located where embryonic remnants of Wolffian ducts are detected, such as the uterine cervix. The information about these tumors, their treatment protocol, and prognosis are scarce.Case report A 60-year-old woman with postmenopausal vaginal bleeding was initially diagnosed with endometrial carcinoma. After suspicion co-testing, the patient underwent a loop electrosurgical excision of the cervix and was eventually diagnosed with mesonephric adenocarcinoma. She was subjected to a radical hysterectomy, which revealed International Federation of Gynecology and Obstetrics (FIGO) IB1 stage, and adjuvant radiotherapy. The follow-up showed no evidence of recurrence after 60 months.Conclusion We present the case of a woman with cervical mesonephric adenocarcinoma. When compared with the literature, this case had the longest clinical follow-up without evidence of recurrence, which reinforces the concept that these tumors are associated with a favorable prognosis if managed according to the guidelines defined for the treatment of patients with cervical adenocarcinomas. Though a rare entity, it should be kept in mind as a differential diagnosis for other cervical cancers.
Keywords: cervix; embryonic remnants; neoplasia